Extracellular Matrices as Bioactive Materials for In Situ Tissue Regeneration - Peng Zhao; Fengbo Yang; Xiaoli Jia; Yuqin Xiao; Chao Hua; Malcolm Xing; Guozhong Lyu (Pharmaceutics, 2023)
Bioactive materials based on a nature-derived extracellular matrix (NECM) represent a category of biomedical devices with versatile therapeutic applications in the realms of tissue repair and engineering. With advancements in decellularization technique, the inherent bioactive molecules and the innate nano-structural and mechanical properties are preserved in three-dimensional scaffolds mainly composed of collagens. Techniques such as electrospinning, three-dimensional printing, and the intricate fabrication of hydrogels are developed to mimic the physical structures, biosignalling and mechanical cues of ECM. Until now, there has been no approach that can fully account for the multifaceted properties and diverse applications of NECM. In this review, we introduce the main proteins composing NECMs and explicate the importance of them when used as therapeutic devices in tissue repair. Nano-structural features of NECM and their applications regarding tissue repair are summarized. The origins, degradability, and mechanical property of and immune responses to NECM are also introduced. Furthermore, we review their applications, and clinical features thereof, in the repair of acute and chronic wounds, abdominal hernia, breast deformity, etc. Some typical marketed devices based on NECM, their indications, and clinical relevance are summarized.